The Dominance of Representative and Directive Speech Acts in Novels: Patterns, Functions, and Their Implications in Literary Pragmatics - Komang Widiani; Made Gautama Jayadiningrat (International Journal of Language and Literature, 2024)
The study of illocutionary speech acts in novels is part of pragmatic research that examines the function of utterances in character communication and their role in structuring narratives. This study employs a Systematic Literature Review (SLR) approach to analyse previous research on illocutionary speech acts in novels. Data were collected from various academic sources and analysed thematically. The findings indicate that representative and directive speech acts are the most dominant types in novels. Directive speech acts, such as commands, requests, advice, and pleas, frequently appear in character interactions, while representative speech acts play a role in conveying information and shaping the narrative. Analysing ten selected studies revealed a consistent pattern in the use of speech acts, with most research employing a qualitative approach and pragmatic discourse analysis. Some studies also highlight how social and cultural contexts influence the interpretation of speech acts in novels. These findings reinforce that illocutionary speech acts not only serve as a means of communication between characters but also function as fundamental elements in narrative dynamics, reflecting broader social realities. The implications of this study are expected to contribute to pragmatic research in literature and enrich the understanding of communication strategies in fictional works.